1989
DOI: 10.1073/pnas.86.10.3494
|View full text |Cite
|
Sign up to set email alerts
|

Trans-activation by thyroid hormone receptors: functional parallels with steroid hormone receptors.

Abstract: The effects of thyroid hormones are mediated through nuclear receptor proteins that modulate the transcription of specific genes in target cells. We previously isolated cDNAs encoding two different mammalian thyroid hormone receptors, one from human placenta (hTRI3) and the other

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…1, the three TRs are least similar at their amino termini. Although this region does not appear to be required for transcriptional activation of a TREpal-containing reporter gene by TR#31 (77), this situation may be analogous to the A and B forms of the progesterone receptor, which differ only in their amino termini yet differentially activate target genes (78). The amino terminal "T-l" domain of the glucocorticoid receptor (79) also modulates transcriptional activation.…”
Section: Discussionmentioning
confidence: 99%
“…1, the three TRs are least similar at their amino termini. Although this region does not appear to be required for transcriptional activation of a TREpal-containing reporter gene by TR#31 (77), this situation may be analogous to the A and B forms of the progesterone receptor, which differ only in their amino termini yet differentially activate target genes (78). The amino terminal "T-l" domain of the glucocorticoid receptor (79) also modulates transcriptional activation.…”
Section: Discussionmentioning
confidence: 99%
“…Dilutions were made in RPMI 1640 medium. Thompson et al showed that the transcriptional activities of thyroid hormone receptors α and β are dose dependent from 1 to 100 nM T3 [20], while the threshold T3 concentration for non-genomic effects ranges from 0.1 to 30 nM [21]. Therefore, 0.1 to 100 nM T3 was used for pre-incubation in most experiments in the study.…”
Section: Cell Culturementioning
confidence: 99%
“…Lastly, hT3R␤1, which does not contain a cluster of basic amino acids in the A/B region corresponding to amino acids 21 to 30 of cT3R␣, binds TFIIB less efficiently than cT3R␣ (35). This may explain the finding that hT3R␤1 activates transcription less efficiently than hT3R␣1 (71), which has the same basic sequence in the A/B region as cT3R␣.…”
mentioning
confidence: 98%
“…Thus, three T3Rs which primarily differ in the A/B domain are expressed, suggesting that this region may play a role in mediating different effects of these receptors. For example, hT3R␣1 has been suggested to be more active in transfection experiments than hT3R␤1 (71).…”
mentioning
confidence: 99%